Angiogenic Properties of Menstrual Stem Cells Are Impaired in Women with a History of Preeclampsia. (27th January 2019) - Varas-Godoy, Manuel; Acuña-Gallardo, Stephanie; Venegas-Duarte, Sebastian; Hill, Charlotte; Caceres-Verschae, Albano; Realini, Ornella; Monteiro, Lara J.; Zavala, Gabriela; Khoury, Maroun; Romero, Roberto; Rice, Gregory; Illanes, Sebastian E.
Abstract : Preeclampsia is a pregnancy-specific disorder defined by the new onset of hypertension and proteinuria after 20 weeks of gestation. Although its precise etiology is still unknown, there is evidence suggesting that it may be a consequence of impaired decidual and stromal cell function. Recently, a stem cell population derived from endometrial tissue and isolated from menstrual effluent called menstrual stem cells (MenSCs) has been identified. MenSCs exhibit important angiogenic and inflammatory properties that may contribute to both normal and pathological complications of implantation and placentation, including preeclampsia. We hypothesized that the angiogenic and inflammatory activity of MenSCs is altered in women who have a past history of preeclampsia and that this phenotype persists postpartum. The primary outcome measures were stromal progenitor cell formation, in vitro induction of endothelial tube formation, and release of proinflammatory cytokines. MenSCs obtained from women with a previous normal or preeclamptic pregnancy displayed similar phenotypic characteristics, tri-differentiation capacity, and proliferation. MenSCs derived from women who had preeclampsia on their previous pregnancy had reduced angiogenic capacity (~30% fewer junctions and nodes, p < 0.05 ) and stromal progenitor cell formation (<50% measured at a serial dilution of 1 : 10.000, p < 0.05 ) when compared to controls. In vitro, MenSCs obtained from patients with a history of preeclampsia expressed less endoglin and secreted less VEGF but more IL-6 than controls did. These data are consistent with the hypothesis that the angiogenic and inflammatory properties of MenSCs of women with a previous pregnancy complicated by preeclampsia have reduced angiogenic capacity and are more proinflammatory than those of MenSCs of women with a previous normal pregnancy. This altered phenotype of MenSCs observed following preeclampsia could either be present before the development of the pathology, predisposing the endometrial milieu to and consequently leading to limited vascular remodeling, or be a consequence of preeclampsia itself. The former may afford opportunity for targeted therapeutic intervention; the latter, a putative biomarker for future risk of pregnancy complications.